Strathening Critical Thinking Skills thought a Problem Based Learning Approach in Elementary Schools in Salatiga City - Kartika, Ranindya Candra; Sumardjoko, Bambang; Rahmawati, Fitri Puji (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The purpose of this study is to describe in depth the learning experience and the effectiveness of using problem-based learning in fostering students’ capacity for critical thinking at Sidorejo Lor 03 Primary School in Salatiga City. Methodology: This research employs a qualitative methodology with a phenomenological design. Data were collected through in-depth interviews with teachers and learners, participatory observation during the learning process, and documentary analysis of related learning materials. Results: The study reveals that problem-based learning provides meaningful learning experiences and significantly enhances students' critical thinking skills. Through real-world problem scenarios, learners become more active in finding information, analyzing problems, and evaluating solutions. Additionally, they demonstrate improved communication, collaboration, and creativity. Applications/Originality/Value: These findings highlight the effectiveness of problem-based learning as an instructional strategy to develop 21st-century skills especially critical thinking in elementary education. The study underscores the value of engaging students with authentic problems t